"Classroometrics": The Validity, Reliability, and Fairness of Classroom Music Assessments. (March 2020) - Wesolowski, Brian C.
Validity, reliability, and fairness are three prominent indicators for evaluating the quality of assessment processes. Each of the indicators is most often written about and applied in the context of large-scale assessment. As a result, the technical properties of these indicators make them limited in both their practicality and relevance for classroom assessments. The purpose of this article is to describe validity, reliability, and fairness in a way that is meaningful and applicable toward improving the quality of classroom music assessments.